2006
DOI: 10.1002/bip.20526
|View full text |Cite
|
Sign up to set email alerts
|

A transmembrane helix‐bundle from G‐protein coupled receptor CB2: Biosynthesis, purification, and NMR characterization

Abstract: The cannabinoid receptor subtype 2 (CB2) is a member of the G-protein coupled receptor (GPCR) superfamily. As the relationship between structure and function for this receptor remains poorly understood, the present study was undertaken to characterize the structure of a segment including the first and second transmembrane helix (TM1 and TM2) domains of CB2. To accomplish this, a transmembrane double-helix bundle from this region was expressed, purified, and characterized by NMR. Milligrams of this hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…A large body of literature supports the basic assumption of the model: For example, proteolysis of membrane proteins resulted in fragments containing entire TM sequences (Huang et al 1981), and chemically or recombinantly synthesized TM peptides spontaneously assembled thereby rescuing receptor activity (Kahn and Engelman 1992;Ridge et al 1995;Martin et al 1999;Wrubel et al 1994). Finally, peptides corresponding to the N and C terminus (Harmar 2001;O'Hara et al 1993), loop domains (Bennett et al 2004;Katragadda et al 2001a, b;Yeagle et al 2000) and transmembrane domains (Katragadda et al 2001a, b;Cohen et al 2008;Zheng et al 2006;Musial-Siwek et al 2008;Tian et al 2007;Lau et al 2008;Mobley et al 2007;Neumoin et al 2007) from GPCRs have been found to fold to distinct secondary structures which in certain cases resembled the structures of the corresponding regions of the intact receptor.…”
Section: Introductionmentioning
confidence: 67%
“…A large body of literature supports the basic assumption of the model: For example, proteolysis of membrane proteins resulted in fragments containing entire TM sequences (Huang et al 1981), and chemically or recombinantly synthesized TM peptides spontaneously assembled thereby rescuing receptor activity (Kahn and Engelman 1992;Ridge et al 1995;Martin et al 1999;Wrubel et al 1994). Finally, peptides corresponding to the N and C terminus (Harmar 2001;O'Hara et al 1993), loop domains (Bennett et al 2004;Katragadda et al 2001a, b;Yeagle et al 2000) and transmembrane domains (Katragadda et al 2001a, b;Cohen et al 2008;Zheng et al 2006;Musial-Siwek et al 2008;Tian et al 2007;Lau et al 2008;Mobley et al 2007;Neumoin et al 2007) from GPCRs have been found to fold to distinct secondary structures which in certain cases resembled the structures of the corresponding regions of the intact receptor.…”
Section: Introductionmentioning
confidence: 67%
“…Probably, even greater insights could be obtained from the analyses of larger substructures or even whole receptors. At this purpose, Zheng and coworkers biosynthesized a quite large segment of the cannabinoid CB 2 receptor, including TM1, IL1 and TM2, using a fusion protein overexpression strategy [50]. The preliminary results gathered by the authors for the 13 C/ 15 N labeled peptide argue in favor of the applicability of this strategy to the synthesis of GPCR helical bundles for NMR studies.…”
Section: Determination Of the 3d Structure Of Gpcrsmentioning
confidence: 99%
“…We previously showed high level expression of fusion proteins when TrpLE was fused to the N terminal of other CB2 fragments [12,14,15]. In the current study, the human CB2 271-326 fragment was fused with TrpLE and the fusion protein was exclusively achieved in the form of IBs in E. coli cells.…”
Section: Resultsmentioning
confidence: 72%
“…Our lab has previously over-expressed, purified and structurally characterized CB2 fragments, including CB2 180-233 , CB2 , and CB2 , which correspond to TM1-IL1-TM2 (from the first transmembrane domain to the second intracellular loop and the second transmembrane domain), TM2 and TM5-IL3 [12][13][14][15] respectively. In these publications, the CB2 fragments were expressed as fusion proteins with a modified TrpΔLE1413 (TrpLE) leader sequence and a 9-histidine tag at the N-terminus.…”
mentioning
confidence: 99%